A Child’s Language Acquisition: The Metathesis Phenomena - khafidhoh khafidhoh (Metathesis: Journal of English Language, Literature, and Teaching, 2019)
Metathesis is one of the unique phenomena among the children during their language acquisition phase. This research aims at investigating the metathesis phenomena happens in a child. The research method used in this research is qualitative method, especially case study. The results of this research show that the metathesis phenomena happen in that child is related to 16 phonemes. It includes pure metathesis in the same syllable phonemes, pure metathesis in the different syllables phonemes, metathesis followed by phonemes addition, metathesis followed by phonemes omission, and metathesis followed by both of them. The findings from this research will be the basis in conducting the following relevant studies.